2010
DOI: 10.1016/j.specom.2009.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The Nijmegen Corpus of Casual French

Abstract: This article describes the preparation, recording and orthographic transcription of a new speech corpus, the Nijmegen Corpus of Casual French (NCCFr). The corpus contains a total of over 36 hours of recordings of 46 French speakers engaged in conversations with friends. Casual speech was elicited during three different parts, which together provided around ninety minutes of speech from every pair of speakers. While Parts 1 and 2 did not require participants to perform any specific task, in Part 3 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
13

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

5
5

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 15 publications
3
34
0
13
Order By: Relevance
“…When assessing the casualness of the speech in their corpus, Torreira, Adda-Dekker and Ernestus (2010) showed that disfluencies (hesitations, false starts and repetitions) occur more often in spontaneous speech than in careful (more formal) speech, which is in line with earlier findings (e.g. Shriberg 2001).…”
Section: Formal and Informal Speech Behaviorsupporting
confidence: 78%
“…When assessing the casualness of the speech in their corpus, Torreira, Adda-Dekker and Ernestus (2010) showed that disfluencies (hesitations, false starts and repetitions) occur more often in spontaneous speech than in careful (more formal) speech, which is in line with earlier findings (e.g. Shriberg 2001).…”
Section: Formal and Informal Speech Behaviorsupporting
confidence: 78%
“…It pleas for the use of one single corpus for the investigation of different phenomena in one language, and for the use of corpora collected with the same procedure for the comparison of languages (e.g. the Nijmegen corpora of casual French, Spanish and Czech, which were all collected with the procedure described in Torreira, Adda-Decker & Ernestus, 2010). At the same time, however, we should investigate reduction phenomena with as many different corpora as possible, because they all have their strengths and weaknesses.…”
Section: Discussionmentioning
confidence: 99%
“…These are absent in careful speech and are typically avoided as much as possible in casual speech produced in formal situations (e.g., Torreira et al, 2010). Further, sentence structure tends to be more complex in careful speech than in casual speech (e.g., Biber 1988; Biber et al 1998).…”
Section: Differences At the Syntactic Levelmentioning
confidence: 99%